The Moscow Offensive - Brown, Dale 1956- (New York, NY : William Morrow, an imprint of HarperCollins Publishers, 2018)
"America's first line of defense--Brad McLanahan and the heroes of the Iron Wolf Squadron--must counter a dangerous Russian strike from within the homeland in this cutting-edge tale from the New York Times master of the high-tech military thriller, Dale Brown. On a remote island estate, a billionaire investor sells his air freight company to a mysterious new owner. The purchaser is none other than the President of Russia, Gennadiy Gryzlov. The Russians will use these private planes to secretly transport dangerous cargo into the United States. The inept American President Stacy Anne Barbeau has failed to account for the Russian threat. But others have been vigilant and will not leave America defenseless. Brad McLanahan and the Iron Wolf Squadron have joined forces with the newly formed Alliance of Free Nations in Eastern Europe, to prepare for the attack they know is imminent. Working with the most cutting-edge technology, the team will deploy CIDs--Cybernetic Infantry Devices--twelve-foot-tall humanoid combat robots, each armed with more firepower than a conventional platoon. But their state-of-the-art weapons may not be enough to combat the threat. The Russians have managed to reverse engineer their own combat robots nearly decimated in a previous attack, and have slowly begun smuggling them across America's borders. Dealing with an unprecedented danger and a feckless president and congress, McLanahan and the Iron Wolf Squadron will once again put their own lives on the line to check this new Russian peril and keep the home of the brave and the free world safe"--
"In this newest installment in the New York Times bestselling series, the Iron Wolf Squadron faces off against the Russian threat, now brandishing a terrifying new weapon"--
Booklist
Kirkus Reviews
Publishers Weekly
Adult
Keywords: Special operations (Military science) -- Fiction; Special forces (Military science) -- Fiction; Terrorism -- Fiction -- Prevention; Suspense fiction